2014
DOI: 10.1680/stbu.12.00087
|View full text |Cite
|
Sign up to set email alerts
|

Testing and design protocol of dissipative devices for out-of-plane damage

Abstract: During the past few decades, various technical solutions have been developed to improve the seismic performance of structural connections, as these determine the global response of buildings as much as single structural elements. However, in the case of heritage buildings, standard strengthening systems might have collateral effects owing to their high stiffness in comparison with historic substrata. Furthermore, little technical guidance is given to designers for dimensioning the retrofit of connections. Draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…To design an anti-seismic device, experimental tests and performance checks are crucial. Overviews of existing testing techniques for dissipative devices for damage in masonry buildings due to OOP can be found in (D'Ayala and Paganoni 2014;Paganoni and D'Ayala 2010). As for the strengthening of masonry structures (Paganoni and D'Ayala 2014), also for the improvement of the dissipative behavior, tests are necessary to define the design process.…”
Section: Introductionmentioning
confidence: 99%
“…To design an anti-seismic device, experimental tests and performance checks are crucial. Overviews of existing testing techniques for dissipative devices for damage in masonry buildings due to OOP can be found in (D'Ayala and Paganoni 2014;Paganoni and D'Ayala 2010). As for the strengthening of masonry structures (Paganoni and D'Ayala 2014), also for the improvement of the dissipative behavior, tests are necessary to define the design process.…”
Section: Introductionmentioning
confidence: 99%
“…Early work by Corradi et al (2016) suggested that, by using high-strength steel cords embedded in the mortar joints, a reinforced joint repointing could be formed and test results demonstrated that it is possible to increase the masonry shear capacity using this retrofitting method. A similar approach have been recently applied by other researchers (Babaeidarabad et al 2014;D'Ayala and Paganoni 2014;Wang et al 2016;D'Antino et al 2018;D'Ambra et al 2018;Casacci et al 2019). The basic idea is to use an inorganic matrix (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…According to these documents, the benefits of possible upgrade interventions in terms of seismic performance must be weighed against the impact on the original aesthetic and structural authenticity of the building. A variety of systems are available [10], [11], [12], but technical codes are vague on design procedures and their implementation hardly follows.…”
Section: Introductionmentioning
confidence: 99%